Study on coalbed methane flow characteristics based on fracture network image - ZHANG Yuzhu (Meikuang Anquan, 2021)
The natural fracture network developed in coal body is the main channel for gas migration. It is of great significance to study the influence of the geometric characteristics of fracture network on CBM flow characteristics. In this paper, the random fracture network image was generated by Monte Carlo method, and then the binarized fracture network image was imported into COMSOL. The image function was used to convert the image into calculation domain, and the numerical model of coal seam gas flow was established to analyze the influence of different fracture structures on coal seam permeability. The results show that the permeability of coal seam increases with the increase of fracture length, density and opening, and with the decrease of fracture inclination. Compared with fracture length and density, fracture aperture has the most significant influence on permeability.